Fabricação de biossensor óptico de glicose em alumina anódica porosa - Ferro, Letícia Mariê Minatogau (2016)
Porous anodic alumina (PAA) has been used as platform for the manufacture of optical sensors. Itshows chemical resistance, thermal stability, hardness, biocompatibility, high surface area which facilitates interaction with the analyte and good morphological organization with the possibility to manipulate its pore size. Furthermore, PAA shows optical responses characterized by Fabry-Pérot interferences that can be obtained by photoluminescence and reflectance spectroscopy. Besides the surface of the AAP can be modified by Layer-by-Layer technique (LbL) in order to enhance optical sensors. Changes in Fabry-Pérot interferences can be monitored and analyzed as sensor responses. In this work, LbL film were deposited using hydrochloride polyallylamine (PAH) and glucose oxidase (GOx) for the purpose of manufacturing an optical biosensor for glucose detection. A protective bilayer of PAH and poly (vinyl sulfonic acid) (PVS) was assembled. The growth of the films were monitored by photoluminescence and total reflectance techniques. In addition, biosensor tests were carried out by immersing PAA in glucose solutions with different concentrations in order to check for changes in Fabry-Pérot oscillations. Analyzing the results, orderly growth of LbL film and biosensor response were verified. Results of the biosensor test were characterized by displacements of Fabry-Pérot interferences to shorter wavelengths and by multivariate analysis. Limit of detection determined by qualitative analysis of the Fabry-Pérot oscillations was 0.1 mol.L-1 to both PAA without surface modification and modified PAA. By using partial least squares (PLS) regression, it was possible to determine glucose from 0.1 mol.L-1 with PAA without modification and 0.01 mol.L-1 for PAA with LbL film. Furthermore, it was also verified the viability of using chemometrics to examine Fabry-Pérot interferences obtained with the PAA as an alternative method shown in the literature, which involves concepts of Fabry-Pérot equation.